Hidradenitis suppurativa: current understanding and management - Frew, John W. (Henry Stewart Talks, 2023)
Hidradenitis suppurativa (HS), Acne inversa, Pathophysiology of hidradenitis suppurativa, Treatment of hidradenitis suppurativa, B cells in hidradenitis suppurativa, Epithelialized tunnels, Inflammation in HS, HS Hurley staging, HS outcome measures, HS comorbidities, Novel targets for HS